Application of Load Compensation in Voltage Controllers of Large Generators in the Polish Power Grid - Bogdan Sobczak (Acta Energetica, 2014)
The Automatic Voltage Regulator normally controls the generator stator terminal voltage. Load compensation is used to control the voltage which is representative of the voltage at a point either within or external to the generator. In the Polish Power Grid (PPG) compensation is ready to use in every AVR of a large generator, but it is utilized only in the case of generators operating at the same medium voltage buses. It is similar as in most European Power Grids. The compensator regulating the voltage at a point beyond the machine terminals has significant advantages in comparison to the slower secondary Voltage and Reactive Power Control System (ARNE)1. The compensation stiffens the EHV grid, which leads to improved voltage quality in the distribution grid. This effect may be particularly important in the context of the dynamic development of wind and solar energy.